The archaeology of nucleation in the Old World : spatiality, community, and identity - Gyucha, Attila,; Salisbury, Roderick B., (Archaeopress Archaeology, 2022)
Fourteen papers take advantage of advances in archaeological methods and theory to explore the role of the built environment in expressing and shaping community organization and identity at prehistoric and historic nucleated settlements and early cities in the Old World.